2012
DOI: 10.1242/jcs.089847
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin mobility is increased at sites of DNA double-strand breaks

Abstract: SummaryDNA double-strand breaks (DSBs) can efficiently kill cancer cells, but they can also produce unwanted chromosome rearrangements when DNA ends from different DSBs are erroneously joined. Movement of DSB-containing chromatin domains might facilitate these DSB interactions and promote the formation of chromosome rearrangements. Therefore, we analyzed the mobility of chromatin domains containing DSBs, marked by the fluorescently tagged DSB marker 53BP1, in living mammalian cells and compared it with the mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
147
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(162 citation statements)
references
References 31 publications
14
147
0
1
Order By: Relevance
“…These observations are consistent with findings from studies of global chromatin movement using fluorescently tagged histones which showed that in mammalian cells, chromatin regions damaged by irradiation undergo no or only limited motion in the nucleus [37]. These results have recently been challenged by experiments indicating that DSBs roam a 2-to 3-fold larger nuclear area compared with undamaged chromatin [36]. As in the case of yeast, the mobility of the damaged regions in mammalian cells may depend on the type of lesion, as for example breaks induced by topoisomerase poisons show increased mobility compared with DSBs induced by irradiation [36,38].…”
Section: Insights From Long-term Time-lapse Imaging Of the Ddr In Sinsupporting
confidence: 89%
See 1 more Smart Citation
“…These observations are consistent with findings from studies of global chromatin movement using fluorescently tagged histones which showed that in mammalian cells, chromatin regions damaged by irradiation undergo no or only limited motion in the nucleus [37]. These results have recently been challenged by experiments indicating that DSBs roam a 2-to 3-fold larger nuclear area compared with undamaged chromatin [36]. As in the case of yeast, the mobility of the damaged regions in mammalian cells may depend on the type of lesion, as for example breaks induced by topoisomerase poisons show increased mobility compared with DSBs induced by irradiation [36,38].…”
Section: Insights From Long-term Time-lapse Imaging Of the Ddr In Sinsupporting
confidence: 89%
“…Live-cell imaging has recently emerged as a powerful technique for visualizing and quantifying the DNA repair process over time in single cells. This technique has been elegantly utilized for understanding the spatiotemporal aspects of the DDR such as the mobility of repair proteins [26,27] and their assembly into foci at damage sites [28][29][30], as well as the movements of damaged DNA and chromatin [31][32][33][34][35][36][37][38][39]. In the following sections, we describe these key areas in which live-cell imaging has provided unprecedented insights into the DDR and outline the main experimental techniques used for these analyses.…”
Section: Introductionmentioning
confidence: 99%
“…This explains the increased effect for the tri-modality strategy. Our results can be further explained by a mechanism of interaction of two DNA double-strand breaks induced in close proximity by individual particles which yields chromosome aberrations (Franken et al 2011;Krawczyk et al 2012, Franken and. This mechanism of cell inactivation is suggested to dominate the responses at low doses up to 3 Gy and is most relevant in clinical radiotherapy with fraction doses in this range.…”
Section: Discussionmentioning
confidence: 62%
“…The single-cell resolution complements the analysis of genetic endpoints, such as survival or recombination rates and in vivo biochemical approaches, demonstrating that not only assembly but also disassembly of HR intermediates is critical (Symington and Heyer 2006). Tagging HR proteins and the DNA damage sites they act on revealed unanticipated dynamics not only of the damaged chromosome but also undamaged chromosomes in response to DSB formation (Dion et al 2012;Krawczyk et al 2012;MineHattab and Rothstein 2012). The mechanisms enabling this dynamics are not yet understood, and it is unclear how these processes relate to chromosomal territories (Fig.…”
Section: Regulation and Coordination With Nuclear Structure And Functionmentioning
confidence: 99%